Necessity and solutions for ethical education among teachers in the framework of industrial revolution 4.0 - Van Vu Hong (Revista on line de Política e Gestão Educacional)
At present, the education and training of countries in the world, especially developing countries, strive to globalization from the region to the world. Vietnam is not out of the development of the country, so now Vietnam has developed comprehensive strategies in all areas, especially education - training is of particular concern. Vietnam has been implementing comprehensive educational Reform. In response to that development, the teacher needs a lot of changes in research and teaching, personal development capacity etc. to meet the globalization requirement of education training. Currently, the contingent of teachers in Vietnam has been constantly developing in quantity and quality, continuing to be standardized to better meet social requirements. However, there are some limitations. On the basis of studying the state’s regulatory documents, and the evaluation of educational institutions, in this article, the author has discussed the rationale for building the ethics model of the teacher. From that solutions to build and perfect teachers’ personalities in the context of globalization and international integration.